Arctic Advanced Education and Research - Husebekk, Anne; Ruud, Kenneth; Eikeland, Sveinung; Gotaas, Geir (Palgrave Macmillan, Cham, 2019)
Publisher's terms of use of "author accepted manuscripts (AAMs)": https://www.palgrave.com/gp/journal-authors/aam-terms-v1 Skilled candidates, research results that are useful both immediately and in a longer time frame, innovation and business creation, and the strengthening of the public sector are among the most important societal impacts of a university. In short, universities provide a survival kit in a changing world. The University of Tromsø–The Arctic University of Norway (UiT) has been instrumental in developing the northernmost part of Norway since its inception 50 years ago, and will continue to be so in the foreseeable future. Knowledge and competence originating at UiT has also contributed decisively to the development of Norwegian national Arctic policy. Similarly, international Arctic policy development will benefit greatly from including the perspectives and experiences developed at universities in the circumpolar North.